2006
DOI: 10.1007/s10834-006-9021-z
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Consequences of Faculty Women’s Academic–Parental Role Balancing

Abstract: Academia, Interrole conflict, Interrole facilitation, Parenting, Role balancing,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 102 publications
0
28
0
2
Order By: Relevance
“…Reductions in weekly work hours as well as protection for part-time workers have also been suggested as ways of lowering work hours so that more time can be distributed to the family, as well as aiding in gender equality (Comer and Stites-Doe 2006;Elliott 2003;Gornick and Meyers 2003). In their analysis of workplace flexibility policies, Noonan et al (2007) showed that work at home is associated with an increase in time spent in child care for mothers.…”
Section: A Critique Of Researchmentioning
confidence: 99%
“…Reductions in weekly work hours as well as protection for part-time workers have also been suggested as ways of lowering work hours so that more time can be distributed to the family, as well as aiding in gender equality (Comer and Stites-Doe 2006;Elliott 2003;Gornick and Meyers 2003). In their analysis of workplace flexibility policies, Noonan et al (2007) showed that work at home is associated with an increase in time spent in child care for mothers.…”
Section: A Critique Of Researchmentioning
confidence: 99%
“…Other factors such as gendered family circumstances, household responsibilities, and personal priorities also enlarge this gap (Comer & Stites-Doe, 2006). …”
Section: The Gender Gap In Academiamentioning
confidence: 99%
“…These are tested later in the models. The following description obviously presents an idealized picture of scientific work that is not representative of all scientific positions, types of institutions, workplaces or fields (Comer/Stites-Doe 2006).…”
Section: Reasons For High Childlessness Among Female Researchersmentioning
confidence: 99%